Civil Disobedience in the Movies as an Example of Politics in Pop Culture - Garczewska, Anna (The Copernicus Journal of Political Studies, 2018)
The law cannot justify breaking the law, but it does not mean that law must be blindly followed. For law to be effective it takes more than just written rules and enforcement agencies. It takes people who respect it. It takes socjety understanding social contract. It takes civil society. Society strong enough to notice when the law or authorities are unfair, unjust against rationality or simply not effective because of a lack of social acceptance. Civil disobedience is a social conscience in action. It’s transcendental and makes perfect movie material, therefore acts of resistance against law and government fill popular culture. One may not accept civil disobedience, treat it as a crime, undermine its legal and moral basis, but cannot notice that nowadays this sort of resistance plays an important part in legal, social and cultural changes around the world. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762